Prevalence of oral conditions and feasibility of self-reported oral conditions (SROC) questionnaire for screening voluntary blood donors - Chenna, Deepika; Acharya, Karthik; Piplani, Angela; Pentapati, Kalyana; Shastry, Shamee (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: To evaluate the prevalence of oral conditions and the feasibility of a questionnaire for self-reporting of oral conditions (SROC) for screening blood donors. Methods: We conducted a cross-sectional survey among voluntary blood donors after fulfilling the blood donation criteria in out-reach blood donation camps. A self-administered questionnaire was designed in English to capture information on demographics (age and sex) and SROC. A trained and calibrated dentist performed a clinical oral examination (decayed teeth, pulpal involvement, periodontitis (pockets, recession, or mobility), pericoronitis, abscess, or purulent discharge) using a mouth mirror and probe under artificial illumination. The blood collected from donors with active oral conditions and potential for bacteremia were sent for bacterial culture and sensitivity. Results: A total of 351 voluntary blood donors participated with a mean age of 39.12 (10.2). Clinical examination showed that decayed teeth (59%) were the most prevalent oral condition, followed by periodontitis (29.1%) and decay with pulpal involvement (25.9%). The sensitivity and specificity for self-reported decayed teeth was 63.8% and 95.8%, respectively. The SROC addressing pain in gums and teeth showed above 80% specificity against decayed teeth (81.9%), decayed teeth with pulpal involvement (82.3%), and periodontitis (82.7%). The specificity values for SROC addressing gum disease and infections in the mouth against periodontitis were 72.7 and 77.1%, respectively. Conclusions: Decayed teeth, periodontitis, and tooth decay with pulpal involvement were common oral conditions among blood donors. SROC may be adopted to aid in identifying donors and to re-evaluate for blood donation to implement safe practices.